2020
DOI: 10.21467/preprints.49
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic and Nutritional Potential of Spirulina in Combating COVID-19 Infection

Abstract: Human history has witnessed various pandemics throughout, and these cause disastrous effects on human health and country’s economy. Once again, after SARS (Severe Acute Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome), the world is observing a very tough time fighting an invisible enemy, the novel COVID-19 coronavirus. Initially observed in the Wuhan province of China, now, it has spread across 210 countries. Number of corona affected confirmed cases have reached > 3 million globally and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Studies have indicated that these microalgae have potent antiviral activities. Calcium spirulan is a polysaccharide derived from spirulina, which inhibits the replication of several viruses, such as influenza, mumps, and HIV [ 35 ]. Furthermore, S. platensis could activate the immune system against viruses through the activation of immune cells and inducing the production of interferon-gamma, which is an important cytokine with antiviral activity.…”
Section: Microalgae and Covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that these microalgae have potent antiviral activities. Calcium spirulan is a polysaccharide derived from spirulina, which inhibits the replication of several viruses, such as influenza, mumps, and HIV [ 35 ]. Furthermore, S. platensis could activate the immune system against viruses through the activation of immune cells and inducing the production of interferon-gamma, which is an important cytokine with antiviral activity.…”
Section: Microalgae and Covid-19 Treatmentmentioning
confidence: 99%
“…Phycocyanin is also a pigment obtained from spirulina and an inhibitor of NADPH oxidase with anti-inflammatory activity. It seems that microalgae (especially Spirulina) are effective candidates for the adjuvant therapy of COVID-19 patients [ 35 ].…”
Section: Microalgae and Covid-19 Treatmentmentioning
confidence: 99%
“…Moreover, studies suggested that Spirulina may be safe for managing influenza outbreaks, however, additional investigations are needed. [80][81][82].…”
Section: Plants and Phytochemicalsmentioning
confidence: 99%
“…However, as recommended by Pendyala and Patras ( 2020 ), further in-vitro and/or in-vivo studies will be crucially needed to support the obtained docking results and unravel the underlying potential of PCB as therapeutic for COVID-19. Additionally, the purified allophycocyanin obtained from Spirulina platensis has been demonstrated to exhibit significant activity against enterovirus 71 (Singh et al, 2020 ). It was observed that the cytopathic effects of the viral infection were neutralized and the viral RNA synthesis was delayed by the microalgal pigment allophycocyanin.…”
Section: Algae; a Treasure-trove Of Bioactive Metabolitesmentioning
confidence: 99%